Editorial. Small and Medium-Sized Entities Reporting In Central and Eastern Europe - Cătălin Nicolae Albu; Karol Marek Klimczak (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This special issue of the journal of Accounting and Management Information Systems groups recent research into reporting by Small and Medium-sized Entities (SMEs) in four countries of Central and Eastern Europe (CEE), namely Poland, Romania, Slovenia and Turkey. SMEs represent the vast majority of entities in many jurisdictions around the world, contribute significantly to the economic development and employ a significant number of staff in their totality, despite overcoming sometimes severe difficulties in accessing funding, staffing or procuring resources to secure their survival and development. The editorial introduces the special issue by outlining the motivation that led to its publication, the common themes and the contribution of the papers presented, and by suggesting some future research avenues in light of recent developments. We strongly encourage our readers to discover the commonalities and differences that characterize the business and reporting environment of SMEs across the CEE region, as well as the diversity of approaches and practice existing in the region.
Keywords: M13; M41; M48; 650; SME; financial reporting; managerial accounting; CEE; European Union; Romania; Poland; Slovenia; Turkey